Controladoria como uma ferramenta de gestão estratégica: o caso da Telemar - Campos, Márcio de Souza (2002)
The present study has the purpose to explain the role of the Controlling Interest in an office where it is demand for all the areas involved in the company looking forward to establish results by the Manager advice. The Controlling Interest as a tool of strategic management has taken Telemar Norte Leste S/A as its application field - Telemar, a company which appeared with the privatization State System of Telecommunications. Telemar has started its activities doing a huge program on quality and universalization goals by the Telecommunications Agency - ANATEL. Demands for the Telemar setters, relating to the refund of the capital spent establish a new way of producing an organization with the introduction of the Better Result Programo In this context have been discussed in details Goals Programs establishesd by Telemar Norte Leste SI A - TELEMAR; the manager tool option, of the EBITDA, the idea of a strategy for the employees involvement, the rise of the intrinsic strengths of the organization, the periodic news of the program results and the distribution of individual bonus for all the employees. The development of the search is based in a methodology in which get together bibliography, document and camp means with quality data treatment in a delimeted of a study category case.